Differences between the rhizosphere microbiome of Beta vulgaris ssp. maritima—ancestor of all beet crops—and modern sugar beets - Zachow, Christin; Müller, Henry; Tilcher, Ralf; Berg, Gabriele (Frontiers in Microbiology, 2014)
The structure and function of the plant microbiome is driven by plant species and prevailing environmental conditions. Effectuated by breeding efforts, modern crops diverge genetically and phenotypically from their wild relatives but little is known about consequences for the associated microbiota. Therefore, we studied bacterial rhizosphere communities associated with the wild beet B. vulgaris ssp. maritima grown in their natural habitat soil from coastal drift lines (CS) and modern sugar beets (Beta vulgaris ssp. vulgaris) cultivated in CS and potting soil (PS) under greenhouse conditions. Analysis of 16S rRNA gene fingerprints and pyrosequencing-based amplicon libraries revealed plant genotype- and soil-specific microbiomes. Wild beet plants harbor distinct operational taxonomic units (OTUs) and a more diverse bacterial community than the domesticated sugar beet plants. Although the rhizospheres of both plant genotypes were dominated by Proteobacteria and Planctomycetes, 47.4% of dominant OTUs were additionally detected in the wild beet rhizosphere. Analysis of the cultivable fraction confirmed these plant genotype-specific differences at functional level. The proportion of isolates displayed in vitro activity against phytopathogens was lower for wild beet (≤45.8%) than for sugar beet (≤57.5%). Conversely, active isolates from the wild beet exhibited stronger ability to cope with abiotic stresses. From all samples, active isolates of Stenotrophomonas rhizophila were frequently identified. In addition, soil type-specific impacts on the composition of bacterial communities were found: Acidobacteria, Chloroflexi, and Planctomycetes were only detected in plants cultivated in CS; whereas Bacteroidetes and Proteobacteria dominated in PS. Overall, in comparison to modern sugar beets, wild beets were associated with taxonomically and functionally distinct microbiomes.